A Cross-Age Study on the Understanding of Chemical and Physical Change and Their Components - Akgun, Abuzer; Aydin, Murat (Asian Journal of Chemistry, 2010)
The purpose of this study involves alternative ideas and misconceptions of the students play an important role in the studies of chemistry education in science. The basis of the chemistry education is constructed at schools through having the students understanding and the concepts of melting, dissolution, evaporation and chemical-physical change. The cross-age study was conducted with a total of 160 student (98 male, 62 female) aged 11, 12, 13 and 14 from 6th, 7th and 8th grades of Atakent elementary school in Adiyaman during 2008-2009 school year. Each group consists of 40 students. The questions related to melting, dissolution, the transformation of matter, chemical-physical changes and mixture topic were chosen from the science curriculum. The first test was the application test which assessed how to prepare the students for these subjects. The second test, named as the theoretical test, consisted of questions which seek the same answers related the same topics. In this cross-age study, the changes in the mental development and knowledge of the students were investigated. The 13 and 14 years-old students provided the best results among the age groups of 11, 12, 13, 14.